Terms of Trade Instability, Economic Vulnerability and Economic Growth: The Role of Institutions in Sub-Saharan Africa - Zaouali, Sana; Zaouali, Amira (Asian Economic and Financial Review, 2015)
Economists have a long argue that institutions and implementation of good governance are important for economic growth. The main objective of this research is to demonstrate that one of positive institutions effects is its ability to mitigate the negative effect of economic vulnerability linked to terms of trade fluctuations on economic growth. The impact of the economic vulnerability and implementation of good governance is estimated for a panel of 15 Sub-Saharan-Africa countries over the period 1996-2011. The results show that good institutional quality helps to undermine the negative effects of economic vulnerability on economic growth. It is also clear from this analysis that the interaction terms between trade openness and institutions can reduce the negative effects of economic vulnerability and that trade openness has a positive effect on economic growth only until a certain level of institutional quality.